Psychosocial Health Implications of Rape as Expressed by Rape Victims in Kwara State, Nigeria - JAMES, Joke Felicia; BUSHARI, Aishat Damilola; JAMIU, Abdulqudus Tosin (Ilorin Journal of Education, 2024)
This study investigated the implications of rape on psychological and social health, as expressed by rape victims in Kwara State, Nigeria. The purpose of the study was to investigate whether; phobia; insomnia and hyper-sexuality are psychosocial implications of rape. Descriptive research design of survey type was adopted for the study. Population comprised all rape victims in Kwara state, Nigeria. Purposive sampling technique was used to select (150) rape victims in Kwara State through a link. A researcher-designed validated questionnaire was used for data collection. A co-efficient of r = 0.82 was obtained through split half method for the reliability test. Inferential statistics of Chi-square (χ2) was used to analyze the data gathered at 0.05 level of significance. The result showed that; phobia, with χ2 value of (44.92) greater than the critical χ2 value of (7.81), while insomnia has χ2 value of (38.68) greater than critical χ2 value (7.81), and hyper-sensitivity has calculated. χ2 value (65.68) greater than the table value (7.81). All the three null hypotheses were rejected and alternative hypotheses upheld. The study concluded that phobia, insomnia, and hyper-sexuality are implications of rape among rape victims in Kwara State Majority of the respondents (84.0%) reported having some sexual related phobias; 84% has insomnia and 83.0% acknowledged to have hyper-sexuality. The researchers recommend that, rape victims should endeavor to visit the hospital or therapists for proper treatments in order to control and manage the side effects resulting from rape.